Migration behaviour of silver eels (Anguilla anguilla) in a system with a continuous transition from river, over estuary to the sea. ... - Verhelst, Pieterjan; Winter, Erwin; Reubens, Jan; Coeck, Johan (MDA, 2025)
Silver eel migration tracking studies are often conducted in systems that are obstructed by mankind. In this study, we track silver eels from a freshwater river, into an estuary and subsequently the North Sea. Silver eels do not encounter any migration barrier during their downstream migration movement. ...